Strategies Ways Of the Office Of the Accountant General Of the Federation's Perspective On the Methods Of Forensic Accounting, Fraud Detection, and Control in Federal Capital Territory Nigeria. - Sulaiman, T.H; Ajiteru, S.A.R; Abalaka, J.N (International Journal of Economics, Commerce, and Management, 2025)
This research empirically investigates the important distinction between fraud identification and forensic accounting in the Nigerian public sector. The study utilized a research survey design with a sample size of 100 respondents, including accountants and auditors from four ministries selected from the Federal Capital Territory (FCT) of Abuja, Nigeria. The primary statistical method employed to test the hypotheses was Analysis of Variance (ANOVA). The research found that forensic accounting is an effective tool in detecting fraud within the Nigerian public sector. It was also revealed that there is a strong correlation between forensic accounting and litigation support services, which play a crucial role in Nigerian courts in handling fraud cases. Additionally, the study highlights the role of forensic accounting in preventing fraudulent activities by enhancing transparency and accountability. Based on the findings, the study recommends that the public sector adopts a robust and transparent accounting system that ensures effectiveness in fraud detection and prevention. Furthermore, there is a need for continuous improvement in the internal control systems within government agencies to detect and prevent fraudulent behavior proactively. The research also stresses the importance of public sector officials embracing core values such as integrity, objectivity, fairness, and accountability in their operations. Finally, it is crucial for forensic accountants to receive specialized training in forensic accounting techniques and procedures to better detect and resolve fraud cases in the public sector. These actions will contribute to reducing fraud levels and improving the overall governance of Nigeria’s public sector.